Pengembangan Media Pembelajaran Interaktif Dalam Mata Pelajaran Dasar-Dasar Desain Komunikasi Visual - May Danisa; Masduki Zakarijah (Department of Electronics and Informatics Engineering Education, 2023)
This study aims to develop and determine the feasibility analysis of interactive learning media in the subjects of Basics of Visual Communication Design which is used as a learning medium at SMK Negeri 1 ROTA Bayat. The research method used is Research and Development with the ADDIE development model. Data collection technique using questionnaire with research subjects of class X Visual Communication Design students at SMK Negeri 1 ROTA Bayat. The results of the research that has been carried out can be seen that: (1) the development of interactive learning media Basic Photography through the stages of analysis, design, development, implementation, and evaluation, (2) The interactive learning media is suitable for use with a feasibility level assessment based on the assessment of media experts with an average of 90.89% and material expert assessment with an average of 97.92%. Trials on 34 students with an average of 91.68%. In this case, it can be said that this interactive learning media is very feasible to be used as a learning medium at SMK Negeri 1 ROTA Bayat.